Nystagmus in Infantile Pompe Disease: a new feature? - Turco, Emanuela Claudia; Facini, Carlotta; Piccolo, Benedetta; Pisani, Francesco (Acta Biomedica Atenei Parmensis, 2020)
We describe a 3 month-old female floppy infant with hypertrophic cardiomyopathy, serum enzyme levels, which were characterized by an aspartate aminotransferase level of 144 U/l, alanine transaminase 240 U/L and creatine kinase level of 543 U/l. On the basis of the clinical signs and laboratory results,  acid α-glucosidase activity was determined from dried blood spots resulting lower than the normal range (0.2 mmol/L/h: normal reference range: 1,86-21,9 mmol/L/h) and leading to a diagnosis of infantile Pompe disease. She also showed multi-directional nystagmus. Refractive errors, ptosis and strabismus are described in infantile Pompe Disease, while nystagmus is rarely reported before. Therefore with this paper we highlight an atypical ocular symptom, whose uncertain pathogenesis, to be taken into consideration, because by now, with increasing survival with ERT, new phenotypes of Pompe disease are taking shape.